1998
DOI: 10.1298/jjpta.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in the Physical Performance of Older Adults in the Community.

Abstract: The primary purposes of this study were 1) to confirm age-related deterioration of physical performance in older adults longitudinally, and 2) to predict future functional status and mortality by initial level of physical performances. The subjects were 517 older adults examined both in 1992 and 1996 in the Tokyo Metropolitan Institute of Gerontology, Longitudinal Interdisciplinary Study on Aging. The same battery consisting of muscle strength, balance, walking, and manual speed was administered to the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 11 publications
3
64
3
Order By: Relevance
“…As for the result of single-leg stance with eyes open, this parameter value significantly decreased 6 years later for the summer and 5 years later for the winter. The grip strength and single-leg stance are general physical measurement parameters [13,14]. The results of this current study actually demonstrate that the physical fitness of older persons gradually declines as they age.…”
Section: Discussionsupporting
confidence: 50%
“…As for the result of single-leg stance with eyes open, this parameter value significantly decreased 6 years later for the summer and 5 years later for the winter. The grip strength and single-leg stance are general physical measurement parameters [13,14]. The results of this current study actually demonstrate that the physical fitness of older persons gradually declines as they age.…”
Section: Discussionsupporting
confidence: 50%
“…The results demonstrated that elderly adults aged 75 years and over showed a greater decrease in gait speed than did the elderly aged 65 to 74 years. The mean decreases in gait speeds over 4 years in young-old and old-old adults were about 6% and 10%, respectively 30) . A previous cross-sectional study, participants aged 19-102 years, indicated that the age of 62 years coincided with an accelerated decline in the speed of walking.…”
Section: Discussionmentioning
confidence: 92%
“…One longitudinal study showed a significant interaction between age group and normal gait speed in elderly people 30) . The results demonstrated that elderly adults aged 75 years and over showed a greater decrease in gait speed than did the elderly aged 65 to 74 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of physical function of the elderly are becoming more important [6][7][8][9] . Regarding the evaluation of the physical function of the elderly, diminished capabilities are commonly encountered in hand-grip strength, gait velocity, timed up-and-go (TUG) at a comfortable speed, and one leg standing time with eyes open.…”
Section: Introductionmentioning
confidence: 99%